Deconstruction of Hierarchical Liability and Harmonization of Sanctions in Consumer Protection against Expired Food Products - Melinda Melinda; Agustianto Agustianto; Nurlaily Nurlaily (CV. Social Politic Genius (SIGn), 2026)
The circulation of expired food products poses risks to public health because legal subjects are not clearly defined, supervision remains fragmented, and food safety violations are often confined to civil dispute resolution. This study analyzes the hierarchical legal liability of business actors within the food supply chain and formulates a sanctions harmonization model to strengthen consumer protection. It uses normative juridical research with statutory, conceptual, and analytical approaches. The findings show that liability must be allocated according to each actor’s function in the supply chain. Producers are responsible for quality, labeling, and expiry dates from the production stage onward. Distributors are required to exercise due diligence in storage and circulation. Retailers and actors engaged in trading through electronic systems must ensure that products offered to consumers have not expired. In the recovery context, consumer compensation should not be limited to the administrative authority of the Consumer Dispute Settlement Agency but should also be linked to sectoral food law instruments that do not expressly provide a maximum nominal limit. In the criminal law context, Law Number 18 of 2012 remains the principal sectoral basis for the manipulation of expiry dates. However, its limited sanctions require harmonization with the regime under Law Number 8 of 1999 when the elements of the offense are independently proven. This study concludes that consumer protection against expired food products requires layered, proportionate, and integrated sanctions.